The Substance Abuse Program for African-Canadian and Caribbean Youth (SAPACCY): An Innovative Program Serving the Mental Health Needs of African, Caribbean, and Black Youth - Gajaria, Amy; Haynes, Kevin; Kosic, Yolanda; Alexander, Donna (INYI Journal, 2021)
Black youth experience disproportionately poor health outcomes throughout Ontario’s healthcare system, including the mental health and addictions system. The Substance Abuse Program for African Canadian and Caribbean Youth (SAPACCY) at the Centre for Addiction and Mental Health (CAMH) seeks to address this disparity by providing clinical services to youth who identify as Black and/or as having African and/or Caribbean heritage, and their families, who are struggling with problematic substance use and/or mental health concerns. The clinical team works from an Afrocentric, culturally responsive lens to promote recovery and support Black youth in working through their mental health and addiction concerns. The program offers mental health and addictions counselling and psychotherapy, psychiatric consultation, psychoeducation, resource navigation, advocacy, and case management services to assist youth and their families/caregivers in reducing harm, moving toward recovery, and making healthy choices for themselves and their family. This paper will discuss SAPACCY’s approach to helping clients build resilience and resistance to anti-Black racism.